Edwin Wieringa and the Exoticism of the Minds of Indonesian Muslims - Media Zainul Bahri (Al-Albab, 2016)
This article elaborates in-depth the views of Edwin Wieringa on Indonesian Islam. Wieringa is Professor of Indonesian philology with special reference to Islamic cultures at the University of Cologne, Germany. In addition to philology, Wieringa also concerns himself with the Indonesian contemporary Islamic issues. According to Wieringa, various aspects of the minds of Indonesian Muslims in the past and present are always exotic, in the sense of “unique” and “attractive”, and therefore motivates him to examine a lot of things about Indonesian Islam. For Wieringa, Indonesian Muslim cultural exoticism also shows a high civilization that must be appreciated by the Indonesian Muslims themselves. Dozens articles of Wieringa which explore the culture of Islam in this country shows that he has a remarkable contribution to the development of Indonesian Islamic and cultural studies.